Sustainable Approach of Reusing Open Dumping Area by Predicting Long-Term Settlement of Waste Soil - Shariffuddin A.S.; Mohd Pauzi N.I.; Hao G.Y. (Institute of Physics Publishing, 2023)
Compaction; Creep; Forecasting; Atterberg limits; Case-studies; Creep functions; Direct shear; Geotechnical properties; Long term settlement; Sieve analysis; Waste soils; Soils; compaction; compressibility; consolidation; geotechnical property; land reclamation; long-term change; prediction; sieving; soil dynamics; soil property; sustainable development; waste technology; Malaysia; Negeri Sembilan; West Malaysia